KUALITAS PELAYANAN PUBLIK DALAM PENGURUSAN SURAT PINDAH DAN DATANG DI KELURAHAN BAROS KECAMATAN CIMAHI TENGAH KOTA CIMAHI - Yustianti Dwi Pratiwi; Zaenal Abidin AS (Jurnal Caraka Prabu, 2024)
This research aims to find out the quality of community service in processing transfer and arrival documents in Baros Village, Central Cimahi District, Cimahi City. The problems are the community's ignorance (procedures) in arranging transfer and arrival letters, the low level of compliance and obedience of the community in the completeness of the Administration for the Management of Transfer and Arrival Letters, the service provided by the apparatus is slow in serving the community for making transfer and arrival letters. The problem identified in this research is the quality of service in processing transfer letters for residents in Baros Village, Central Cimahi District, Cimahi City. The aim of the research is to find out and assess the quality of service in processing transfer letters for residents in Baros Village, Central Cimahi District, Cimahi City. The research method used in this research is descriptive with a qualitative approach with an inductive case study approach. Data collection techniques through literature study, observation, interviews and documentation. Data analysis techniques include analysis before the field, analysis during the field and analysis after the field. With stages of data collection, editing, statement classification, data entry, testing and data description. Grand theory Arianto(2018:83) Tangible factors, Reliability, Responsiveness, Assurance, Emphaty. The research results show that overall the quality of public services in processing transfer and arrival letters in Baros Village, Cimahi Tengah District, Cimahi City shows that the Tangible, Reliability, Responsiveness, Assurance, Emphaty factors are quite good.